Cellulolytic and mannanolytic aerobic bacteria isolated from Buffalo rumen (Bubalus babalis) and its potency to degrade fiber in palm kernel meal (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sari SLA, Triyanto T, Zuprifal Z, Prijambada ID. 2021. Cellulolytic and mannanolytic aerobic bacteria isolated from Buffalo rumen (Bubalus babalis) and its potency to degrade fiber in palm kernel meal. Biodiversitas 22: 2829-2837. Palm kernel meal (PKM) is potential to be used as feed, but its high fiber content causes PKM meal difficult to be digested by monogastric animals. Ruminants are especially effective in digesting plant fibers because of the presence of microbes in their rumens. Based on those facts, this research was conducted to obtain mannanolytic and cellulolytic bacteria from buffalo rumens (Bubalus babalis, Linnaeus, 1758), which can degrade fibers in PKM. Bacteria were isolated from buffalo rumen by using PKM- isolation media. Screening of hydrolytic activities was done based on clear zone formation on screening media. A total of five bacterial isolates with the highest hydrolytic activities were then assayed quantitatively for their abilities to degrade mannan and cellulose, then identified based on 16S rRNA gene sequences. This research successfully isolated 34 bacterial isolates. The screening result demonstrated that all isolates could hydrolyze mannan, cellulose and polysaccharide in PKM. Isolate BR25 showed the highest hydrolytic ability on PKM and mannan screening media with clear zone diameter/colony diameter ratio (dz/dc ratio) of 2.99 and 3.53, respectively.  Isolate BR31 showed the highest cellulolytic ability with dz/dc ratio value of 2.22. Five isolates with the highest hydrolytic activity, i.e. BR14, BR16, BR23, BR25, and BR30 showed the ability to grow on submerged media which contain locust bean gum (LBG) and microcrystalline cellulose (MCC) respectively, as single carbon source and isolate BR25 showed the highest ability to degrade mannan and cellulose. Based on the gene sequence of 16S rRNA, isolates BR14, BR16, BR23, BR25, and BR30 were identified to be closely related to Exiguobacterium acetylicum, Bacillus cereus, Klebsiella quasipneumoniae, Paenibacillus polymyxa, and Acinetobacter baumannii with 98.57-100% level of similarity.
Keywords: mannolytic, cellulolytic, buffalo rumen, fiber degradation, palm kernel meal.